A Phenomenological Analysis of Students' Digital Emotional Questions (EQ) in the Era of TikTok Dominance - Jannah, Ayu Raudatul; Fitriyah, Imaniyatul (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
The purpose of this study is to analyze the phenomenon of students' digital EQ in the era of TikTok dominance. This study used a qualitative phenomenological approach to explore the experiences of eight students who actively use TikTok. Participants were selected based on purposive sampling with the criteria of using TikTok for at least two hours a day for six months. Information was collected through unstructured interviews and analyzed using thematic analysis. The results showed that six of the eight students had low digital EQ, which was evident in their poor self-awareness and self-regulation, which then impacted their learning motivation. In addition, several students also demonstrated low empathy and social skills when using TikTok. This confirms that students' digital EQ in the era of TikTok dominance has the potential to influence student development, both emotionally and socially.